GENETIC POLYMORPHISMS IN GABA RECEPTORS AND ALCOHOL USE DISORDER SUSCEPTIBILITY: A MULTI-ETHNIC COHORT STUDY (International journal of medical sciences, 2025)
Background: Alcohol use disorder (AUD) demonstrates substantial heritability, with genetic factors accounting for approximately 50-60% of risk variance. The GABAergic system plays a critical role in alcohol's acute effects and chronic adaptations, yet specific genetic variants remain incompletely characterized across diverse populations.Objective: To investigate associations between single nucleotide polymorphisms (SNPs) in GABA receptor genes and AUD susceptibility across multiple ethnic groups, and to examine gene-environment interactions.Methods: We conducted a case-control study involving 2,847 participants (1,523 AUD cases, 1,324 controls) from four ethnic populations: European-American (n=1,156), African-American (n=742), Hispanic/Latino (n=581), and East Asian (n=368). Genotyping was performed for 47 SNPs across GABRA1, GABRA2, GABRA6, GABRB1, GABRG1, and GABRG2 genes. Logistic regression models adjusted for age, sex, and population stratification were employed. Environmental factors including childhood adversity and peer drinking behavior were assessed.Results: The GABRA2 rs279858 polymorphism showed the strongest association with AUD across all ethnic groups (OR=1.68, 95% CI: 1.42-1.98, p=3.2×10⁻⁸). Allele frequencies varied significantly between populations: 0.42 (European-American), 0.38 (African-American), 0.45 (Hispanic/Latino), and 0.31 (East Asian). Significant gene-environment interactions were identified between GABRA2 variants and childhood trauma (p=0.003), with effect sizes strongest among individuals reporting severe adversity (OR=2.34, 95% CI: 1.67-3.28). Haplotype analysis revealed a protective combination in GABRG1 (frequency 0.18, OR=0.64, p=0.001). Age at drinking onset partially mediated genetic effects (indirect effect: β=0.42, p<0.001).Conclusions: GABRA2 polymorphisms confer substantial AUD risk across diverse populations, with effect magnitudes modified by environmental exposures. Findings support precision medicine approaches incorporating genetic profiling and early-life risk factors for AUD prevention strategies.